2015
DOI: 10.1111/ijfs.12881
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in sprouted wheat flour functionality: effect of time, temperature and elicitation

Abstract: This study was aimed at optimising conditions of wheat germination (temperature, time of sprouting and elicitation) to improve its phenolics content, antioxidative capacity and nutritional quality. Total phenolics and antioxidant potential were improved most effectively after 4 days of sprouting at 20°C. The highest reducing ability and the ability to quench free radicals (1.24 mg Trolox equivalent (TE) g À1 d.m. and 0.38 mg TE g À1 d.m., respectively) were determined for 4-day-old control and willow + yeast e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 38 publications
6
35
1
1
Order By: Relevance
“…Our results exhibit that the free form of flavonoids comprise the major component of the total flavonoids. The accumulation of TFC was time-dependent; similar to observations previously recorded in mung bean, radish, broccoli, and sunflower [11]. The flavonoid content in free form was positively correlated with TFC ( r = 1.0) in the two treatments.…”
Section: Discussionsupporting
confidence: 85%
“…Our results exhibit that the free form of flavonoids comprise the major component of the total flavonoids. The accumulation of TFC was time-dependent; similar to observations previously recorded in mung bean, radish, broccoli, and sunflower [11]. The flavonoid content in free form was positively correlated with TFC ( r = 1.0) in the two treatments.…”
Section: Discussionsupporting
confidence: 85%
“…The results are in accordance with Swieca and Dziki () who found the highest antiradical activity at 20°C in comparison those found at 25°C.…”
Section: Resultssupporting
confidence: 92%
“…Possibly because of differences in metabolites and responses of antinutrients in germinated cereals, conflicting reports exist on the effects of germination on glycaemia. Swieca & Dziki (2015) investigated the effects of germination conditions on RS and starch digestibility of wheat and concluded that germination time and temperature were the most important processing conditions. Saleh et al (2013) reported about 30% increase in starch digestibility of millet with germination as carbohydrate availability was improved.…”
Section: Sprouting Germination and Maltingmentioning
confidence: 99%